Assessing Literacy-Awareness, and Participation in Kerala Government Financial Schemes and Support for NRKs, Among Kerala Expatriates in the UAE (International Journal of Food and Nutritional Sciences, 2022)
Expat’swelfare is a vital concern for their home countries. Governments and organizations in these home countries typically establish policies and support mechanisms to ensure the well-being of their expatriate populations. This includes services like consular assistance, legal protection, and access to healthcare and education.Non-Resident Keralites (NRKs), are a subject of paramount importance for both the Kerala government and the expatriate community itself. Kerala has one of the largest diaspora populations in India, with millions of its citizens living and working in various countries around the world. This research study aims to assess the knowledge of various govt schemes and assistance designed for NRKs, among Keralite expats in UAE, 15 each member from Males and females are selected as the population for this study, those whohave been living In UAE for more than 5 years. The collected data were analyses in using statistical measures. Standard Questionnaires were used.